A new species of flea beetle, genus Pedilia Clark (Coleoptera: Chrysomelidae: Galerucinae), from Osa Pennisula, Costa Rica - Duckett, Catherine N. (Zootaxa, 2003)
A new species of Pedilia Clark, P. sirena, from Costa Rica is described and illustrated. This species is monophagous on Passiflora pittieri HBK, and known only from the Sirena area of Parque National Corcovado, Costa Rica, for which it is named. Previous scientific reports mentioning this species are discussed, specifically those treating its ecological interaction with Heliconius hewistoni Staudinger, (Lepidoptera: Nymphalidae). This species is also notable for the two distinctly textured areas of its mandibular mola.